A disciplina Inglês Instrumental no Ensino Superior e as representações de seus professores: um estudo de caso - Araki, Ligia Enomoto (2013)
This research aimed at identifying and analyzing the representations of the ESP teachers on the discipline itself, on the roles of the teacher and on the student, both of them derived from the same context, and on the teaching material used for the discipline. The teaching and learning of ESP has been part of the curriculum of some undergraduate courses in Brazilian universities since the 1970 s. Although the discipline has been consolidated in the country for more than four decades, it is still scarce the studies about representations of the ESP teachers. The theoretical framework of this work consists of the following studies: the teaching and learning of ESP (DUDLEYEVANS e ST. JOHN, 1998; HUTCHINSON e WATERS, 1987; CELANI, 2005; 2009; RAMOS, 2009A); the ESP myths (RAMOS, 2005; 2009b); the roles of the ESP teacher (CELANI, 1998; HOLMES, 1986;1988); the ESP student SCOTT, 1984; SCHLEPPEGRELL e BOWMAN, 1986); the teaching material used in ESP (BASTURKMEN, 2010; DUDLEY-EVANS e ST. JOHN, 1998; HOLMES, 1985; HUTCHINSON e WATERS, 1987; ROBINSON, 1991) and the concept of social representations (MOSCOVICI, 2004). This qualitative research is a study case, based on (STAKE, 1998; GIL, 2010; JOHNSON, 1992; YIN, 2001; CHIZZOTTI, 2006). This paper had the contribution of 15 English teachers who teach or have taught the discipline ESP at undergraduate level. The participants answered two questionnaires in order to investigate and find their representations. The results showed that some of the myths pointed out by Ramos (2005) perpetuated along the decades which proves the lack of formation and development of the participants in the ESP area